Cornerstones in Contemporary Inorganic Chemistry - Gregory, Duncan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A collection of essential research articles and scientific reviews covering some of the most pertinent and topical areas of study that currently constitute Inorganic Chemistry in the early 21st century.